2015
DOI: 10.1021/acs.est.5b02237
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding as an Exposure Pathway for Perfluorinated Alkylates

Abstract: Perfluorinated alkylate substances (PFASs) are widely used and have resulted in human exposures worldwide. PFASs occur in breast milk, and the duration of breastfeeding is associated with serum-PFAS concentrations in children. To determine the time-dependent impact of this exposure pathway, we examined the serum concentrations of five major PFASs in a Faroese birth cohort at birth, and at ages 11, 18, and 60 months. Information about the children’s breastfeeding history was obtained from the mothers. The traje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
107
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 158 publications
(116 citation statements)
references
References 27 publications
9
107
0
Order By: Relevance
“…In terms of magnitude the increase in serum cholesterol observed for both PFOS and PFOA was slightly lower but still comparable to the increase observed among women with high saturated fat intake (see Table 3). In sensitivity analyses the associations between PFOS and PFOA with serum cholesterol were examined among nulliparous (n¼ 490) and parous (n ¼364) women as previous breastfeeding has been shown to be a strong determinant of PFOS and PFOA concentrations (Mogensen et al, 2015). In these analyses similar associations between PFOS and PFOA and serum cholesterol were observed for both nulliparous and parous women (data not shown).…”
Section: Resultsmentioning
confidence: 89%
“…In terms of magnitude the increase in serum cholesterol observed for both PFOS and PFOA was slightly lower but still comparable to the increase observed among women with high saturated fat intake (see Table 3). In sensitivity analyses the associations between PFOS and PFOA with serum cholesterol were examined among nulliparous (n¼ 490) and parous (n ¼364) women as previous breastfeeding has been shown to be a strong determinant of PFOS and PFOA concentrations (Mogensen et al, 2015). In these analyses similar associations between PFOS and PFOA and serum cholesterol were observed for both nulliparous and parous women (data not shown).…”
Section: Resultsmentioning
confidence: 89%
“…Much previous research has focused on pre-natal exposure, but both the pre- and post-natal periods are known to be important in establishing an immune deviation from T H 2 to T H 1 skewed immunity (Romagnani 2014), and in this study, associations were found only with post-natal exposure. In addition, it has been established that children are highly exposed to PFAS in early life through breastfeeding (Mogensen et al 2015), emphasizing the need to further study the effects of post-natal PFAS exposure.…”
Section: Discussionmentioning
confidence: 99%
“…As such, humans are exposed to complex mixtures of contaminants throughout development. Newborn cord blood often contains hundreds of contaminants 18, 19 , and exposure continues via oral routes such as breast-feeding 20, 21 and from inhalation and dermal contact in indoor environments 14, 22–24 in early life.…”
Section: Introductionmentioning
confidence: 99%